Death after sauna—case report of a heat stroke associated subarachnoid hemorrhage - Nothnagel, Anna Maria; Schwartz, Stefan; Abramovich, Igor; Schneider, Thomas; Angermair, Stefan; Treskatsch, Sascha (Frontiers in Cardiovascular Medicine, 2024)
Heat exposure could cause organ injuries leading to multi-organ failure. This case report describes a cardiopulmonary healthy 61-year-old woman who was admitted to our university hospital in an unconscious state after spending more than 30 min in an 80°C sauna. Initial radiological imaging revealed no pathological findings. Laboratory results revealed a rapidly progressing disseminated intravascular coagulation (“DIC”) and a clinically asymptomatic COVID-19 infection. The patient died 38 h after admission due to a second-stage subarachnoid hemorrhage associated with progressive DIC. This report emphasizes the importance of awareness and strategies to mitigate deadly consequences of heat exposure.